The challenge of return to work in workers with cancer: employer priorities despite variation in social policies related to work and health - de Rijk, Angelique (J Cancer Surviv, 2019)
PURPOSE: This study explored employer’s perspectives on (1) their experience of good practice related to workers diagnosed with cancer and their return to work (RTW), and (2) their perceived needs necessary to achieve good practice as reported by employers from nine separate countries. METHODS: Twenty-five semi-structured interviews were held in eight European countries and Israel with two to three employers typically including HR managers or line managers from both profit and non-profit organisations of different sizes and sectors. Interviews were recorded and transcribed verbatim. A grounded theory/thematic analysis approach was completed. RESULTS: Employers’ experience with RTW assistance for workers with cancer appears to be a dynamic process. Results indicate that good practice includes six phases: (1) reacting to disclosure, (2) collecting information, (3) decision-making related to initial actions, (4) remaining in touch, (5) decision-making on RTW, and (6) follow-up. The exact details of the process are shaped by country, employer type, and worker characteristics; however, there was consistency related to the need for (1) structured procedures, (2) collaboration, (3) communication skills training, (4) information on cancer, and (5) financial resources for realizing RTW support measures. CONCLUSIONS: Notwithstanding variations at country, employer, and worker levels, the employers from all nine countries reported that good practice regarding RTW assistance in workers with a history of cancer consists of the six phases above. Employers indicate that they would benefit from shared collaboration and resources that support good practice for this human resource matter. IMPLICATIONS FOR CANCER SURVIVORS: Further research and development based on the six phases of employer support as a framework for a tool or strategy to support workers with a history of cancer across countries and organisations is warranted.